Hospitals, Physicians, and Health Insurers: Guarding Against Implied Agreements in the Health Care Context - Anthony J. Dennis (Washington University Law Quarterly, 1993)
This Article discusses and explores the importance of the federal antitrust laws to the health care industry in the provider network context and then suggests guidelines for avoiding antitrust liability.
Keywords: Antitrust law; Hospitals; Hospitals – Antitrust law; Health insurance